Phenylketonuria: importance of neonatal screening, insights into genotype-phenotype correlations, and novel therapeutic approaches - Djordjevic Milosevic, Maja; Kecman, Bozica; Grkovic, Sanja; Martic, Jelena; Klaassen, Kristel; Stankovic, Sara; Stojiljkovic, Maja (Medical Research, 2026)
Phenylketonuria (PKU) is the most common inborn error of metabolism (IEM) affecting amino acid metabolism among individuals of Caucasian origin, with an incidence ranging from 1:10,000 to 1:20,000 live births. It is inherited in an autosomal recessive manner and results from reduced activity of the enzyme phenylalanine hydroxylase (PAH), leading to the accumulation of phenylalanine and a deficiency of tyrosine. In untreated patients, the clinical phenotype is primarily a consequence of neurotoxicity and includes developmental delay, intellectual disability, and epilepsy. To date, more than 1,100 pathogenic variants of the PAH gene have been identified. The most frequent pathogenic variant reported in Serbia is p.Leu48Ser. Numerous studies have focused on elucidating genotype-phenotype correlations in PKU. Early detection through newborn screening (NBS) programs, based on the identification of elevated phenylalanine concentrations, and prompt initiation of treatment, remains the only effective strategy to prevent intellectual disability and epilepsy and to enable normal neurodevelopment. The introduction of tandem mass spectrometry has significantly expanded the number of IEMs detected by NBS programs across Europe and worldwide. PKU treatment continues on a phenylalanine-restricted diet, which is highly effective but demanding for patients and their families. Adjunct therapeutic approaches include the use of the PAH cofactor tetrahydrobiopterin and enzyme substitution therapy with pegvaliase, aiming to liberalize diet. However, a major limitation of tetrahydrobiopterin therapy is the lack of response in patients with severe phenotypes. The introduction of BH2 (sepiapterin) offers promising prospects for increasing residual PAH activity across different phenotypic groups.
Keywords: phenylketonuria, newborn screening, genotype-phenotype correlation, pegvaliase, sepiapterin